Qualitative Study on the Acceptability of and Adherence to a Vaginal Ring for HIV Prophylaxis Among Adolescent Girls. (1st July 2021) - Baker, Zoë; Javanbakht, Marjan; Moore, Janell; Brosnan, Hannah; Squires, Kathleen; Bunge, Katherine; Zimet, Gregory; Mensch, Barbara; Soto-Torres, Lydia; Kapogiannis, Bill; Levy, Lisa; Hoesley, Craig; et al.
Abstract : Objective: This study aims to assess the product-related, relationship-related, and sex-related factors that act as facilitators and barriers to the acceptability of a vaginal ring (VR) for HIV prevention among adolescent girls. Design: Qualitative study. Methods: Ninety-six girls aged 15–17 years from 6 urban US sites were enrolled in MTN-023/IPM 030, a 24-week randomized controlled trial, for assessing the safety and acceptability of a dapivirine VR for HIV prevention. At week 24, 21 girls were randomly selected to participate in in-depth interviews. Interviews were transcribed verbatim and data analyzed using a thematic analysis approach. Facilitators and barriers to VR acceptability related to participants' relationships, sexual activity, and characteristics of the VR product were identified. Results: Factors related to relationships rarely seemed to act as barriers to VR acceptability; most participants disclosed VR use to sexual partners, and positive reactions from sexual partners, which were common, seemed to facilitate VR acceptability. Emotional and/or physical discomfort surrounding VR use during sex was mentioned occasionally as a barrier to VR acceptability. Product characteristics were most frequently mentioned as barriers to VR acceptability. Many participants reported concerns about the large size of the VR on first impression. Although most found the VR comfortable, some reported pain with VR insertion. Several participants were concerned about VR cleanliness, particularly during menstruation. Conclusion: Product considerations, specifically size and use during menstruation, were the most commonly reported barriers to VR acceptability in this study. Adolescent girls may require additional counseling to assuage product concerns regarding a VR for HIV prevention. Abstract : Supplemental Digital Content is Available in the Text.